2006
DOI: 10.1007/s10853-005-5678-1
|View full text |Cite
|
Sign up to set email alerts
|

Room and high temperature tensile behaviour of a P/M 2124/MoSi2 composite at different heat treatment conditions

Abstract: In the present work, a 2124/15vol%MoSi 2 composite was obtained by powder metallurgy. Its microstructure and mechanical properties were investigated at room and at high temperature (up to 200ºC) in conditions T351, T4 and after heat treatments at 495ºC for up to 100 hours. Up to 150ºC, tensile properties of 2124/MoSi 2 in T351 resulted similar to those of a ceramic reinforced 2124/SiC composite. Yield stress of the 2124/MoSi 2 material, after heating at 495ºC for up to 100 hours, resulted higher than that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The nearly unchanged structure characteristics of the powder at final stages of milling has been attributed to a balance between the plastic deformation via dislocation motion and the dynamic recovery and recrystallization behavior of the material during mechanical milling process. 17 The nanostructure and nano-sized MoSi 2 particles which were produced in this work, are expected not only to have good inherent physical and mechanical properties but also to be an important material for using in metal matrix composites as intermetallic reinforcement, regarding to the some investigations [4][5][6] which reported that MoSi 2 micrometric particles cause significant improvement to the tensile and wear properties of aluminum matrix composites.…”
Section: X-ray Diffraction Evaluationmentioning
confidence: 93%
See 1 more Smart Citation
“…The nearly unchanged structure characteristics of the powder at final stages of milling has been attributed to a balance between the plastic deformation via dislocation motion and the dynamic recovery and recrystallization behavior of the material during mechanical milling process. 17 The nanostructure and nano-sized MoSi 2 particles which were produced in this work, are expected not only to have good inherent physical and mechanical properties but also to be an important material for using in metal matrix composites as intermetallic reinforcement, regarding to the some investigations [4][5][6] which reported that MoSi 2 micrometric particles cause significant improvement to the tensile and wear properties of aluminum matrix composites.…”
Section: X-ray Diffraction Evaluationmentioning
confidence: 93%
“…These elements also offer the longest inherent life of all electric heating elements. [1][2][3][4][5][6] MoSi 2 (Tetragonal) is one of the three intermetallic phases present in the Mo-Si system ( Fig. 1) along with Mo 5 Si 3 (Tetragonal) and Mo 3 Si (Cubic).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of reinforcing particles on the mechanical properties of an MMC is often estimated with the use of the mechanical properties of the annealed alloy being the matrix of this MMC. 17,[21][22][23] However, recrystallization, deposition, or dissolution of various phases may occur during the production of the composite, which are caused by thermal and deformation-induced effects, thus altering the mechanical and plastic properties of the matrix versus those in the annealed state. As a result, conclusions about the quantitative influence of reinforcing particles on mechanical properties may be incorrect due to the use of the erroneous mechanical properties of the MMC matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Intermetallics particles have been used as an alternative because of their lower abrasiveness and brittleness [6][7][8] . Intermetallics have also thermal expansion coefficients closer to the aluminum, resulting in a decrease of the residual stresses in the reinforcement-matrix interface, thus reducing problems related to thermal fatigue 9 . Powder metallurgy (PM) has proved to be a very suitable method for processing of metal matrix composites because it prevents reactions between matrix and reinforcement.…”
Section: Introductionmentioning
confidence: 99%